Outdoor-Based Snakes and Ladder Game: Stimulation of Hyperactive Children - Ulpi, Wahyuni; Pajarianto, Hadi; Riswanto, A. Heri; Junior, Jacinto de Oliveira; Bachtiar, Muhammad Yusri (LETIGES, 2025)
This study explores the use of outdoor-based Snakes and Ladders as an alternative medium for stimulating and shaping the behavior of hyperactive children. Employing a qualitative descriptive approach, the research was conducted with the following subject criteria: (1) children enrolled at ABA II Quranic School Palopo; (2) aged 5–6 years; (3) residing with their parents; and (4) consistently exhibiting symptoms of hyperactivity. Supporting informants included classroom teachers and parents. Data collection techniques utilized source triangulation—comparing data from observations, interviews, and documentation—and member checking, wherein findings were confirmed with participants. The data analysis procedure involved four stages: (1) data collection, (2) data reduction, (3) data display, and (4) conclusion drawing and verification. The findings indicate that the outdoor-based Snakes and Ladders game is an effective behavioral stimulation tool for hyperactive children. The game offers opportunities for physical movement, incorporates structured rules, and fosters an enjoyable learning environment, thereby meeting the developmental needs of children with high activity levels and emerging self-regulation skills. Participation in the game facilitated the development of behavioral competencies, including turn-taking, rule compliance, and impulse control. Additionally, the game supported enhancing social skills such as cooperation, communication, and empathy. The outdoor setting further contributed to these outcomes by providing open space, fresh air, and a relaxed yet engaging atmosphere. The novelty of this research lies in its adaptation of a traditional game into a developmentally appropriate tool for physical and behavioral stimulation that is both flexible and easily implemented.